2022
DOI: 10.1186/s12964-021-00808-w
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: the key of sophisticated cell–cell communication and targeted metastasis in pancreatic cancer

Abstract: Pancreatic cancer is one of the most common malignancies. Unfortunately, the lack of effective methods of treatment and diagnosis has led to poor prognosis coupled with a very high mortality rate. So far, the pathogenesis and progression mechanisms of pancreatic cancer have been poorly characterized. Exosomes are small vesicles secreted by most cells, contain lipids, proteins, and nucleic acids, and are involved in diverse functions such as intercellular communications, biological processes, and cell signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 101 publications
0
19
0
1
Order By: Relevance
“…46 Moreover, drug conjugated AuNPs have a faster drug release. 39 Therefore, drug delivery vehicles that address these issues are still strongly needed. 47,48 The integration of exosomes, the natural NPs, with artificial NPs has become of high interest in the fields of disease diagnostics and treatment due to the exosomes' excellent biocompatibility, long-term circulation, and nonimmunogenicity, which makes them ideal to deliver different types of drugs, RNAs, and proteins.…”
Section: The Necessity Of Nanoparticles To Label Exosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…46 Moreover, drug conjugated AuNPs have a faster drug release. 39 Therefore, drug delivery vehicles that address these issues are still strongly needed. 47,48 The integration of exosomes, the natural NPs, with artificial NPs has become of high interest in the fields of disease diagnostics and treatment due to the exosomes' excellent biocompatibility, long-term circulation, and nonimmunogenicity, which makes them ideal to deliver different types of drugs, RNAs, and proteins.…”
Section: The Necessity Of Nanoparticles To Label Exosomesmentioning
confidence: 99%
“…Exosomes have a major role in cellular communication. The cells are able to communicate between each other by the exchange of exosomes and their cargo. Exosomes also have a significant potential benefit in the diagnosis and treatment of cancer . The exosome-based system has been advanced to deliver the cancer drugs doxorubicin and paclitaxel, as well as RNAs and enzymes, to targeted cancer cells. , Engineering exosomes with dual ligand functionality is essential to increase their therapeutic efficiency.…”
Section: Exosome Biogenesis and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Еще одно перспективное направления в поиске ранних биомаркеров ПАК базируется на современном представлении об этапности развития патология от предраковых изменений до рака (сроки развития PanINs до прогрессирующего рака варьируют вплоть до 10 лет до диагностики РПЖ) и акцентирует внимание не на активности и метаболизме самих раковых клеток, а на активности «опухолевого окружения» -стромальных клеток [68][69][70][71]. Возможно, что раковые клетки и/или окружающие стромальные клетки, в частности панкреатические звездчатые клетки (доминирующие коллаген-продуцирующие клетки стромы ПАК), секретируют факторы, не только ответственные за регуляцию микроокружения РПЖ и микроокружение метастатических очагов, рост и выживание раковых клеток, их метастическое перемещение [72][73][74][75][76][77][78], но и опосредующие развитие инсулинорезистентности и гипергликемии [79][80][81]. Perera CJ с соавт.…”
Section: процедуры скринингаunclassified
“…They are broadly distributed in multiple body fluids, such as blood, urine, cerebrospinal fluid, and bile, and have good stability ( 9 ). Accumulating studies have revealed that exosomes play an essential role in cell–cell communication in the tumor microenvironment, and thus contribute to tumorigenesis and development of a variety of cancers ( 10 , 11 ). In addition, exosomes contain a wide range of components, such as proteins, lipids, nucleic acids, mRNAs, and microRNAs (miRNAs), which are clinically important as diagnostic biomarkers, therapeutic targets, and anti-cancer drug delivery vehicles ( 12 ).…”
Section: Introductionmentioning
confidence: 99%